INVESTIGATION ON THE EFFECT OF ROLL MOTION ON MANEUVERABILITY OF UNDERWATER GLIDER USING WATER BLADDERS - WONG , HAO XIANG (IRC, 2018)
A newly developed novel internal roll mechanism is implemented on the UTP glider where two water bladders are fitted to achieve roll control. The roll motion of the glider is affected by the difference in volume across the two water bladders because of the torque generated by fluid flow. To achieve roll control, a disturbing roll moment is required. However, the presence of hydrodynamic roll moment opposes the roll and returns the glider to its original stable position to achieve lateral stability. Hence, in this work, steady-state Computational Fluid Dynamics (CFD) approach that uses the SST k–ω turbulence model was carried out to study the flow behaviour and to determine the restoring roll moment at three different roll angles for NACA0016 wing configuration. A rectangular shaped fluid domain was constructed around the glider in accordance with ITTC recommendations for CFD marine applications and the glider is subjected to its conventional cruise speed of 0.25 m/s. The required disturbing roll moment was determined by the summation of the restoring roll moment at glider’s initial angle with the moment required to produce a desired angular acceleration. Two linear equations had been developed to ease the computation of the required disturbing roll moment and the value of y-intercept which varies with the glider’s initial angle had been computed in a table. Study shows that a greater disturbing roll moment is required to achieve a bigger roll angle and within a shorter period. The centre of gravity of the glider is determined and is located at approximately 50.2 cm from the nose of the glider.